Analisis Produktifitas Tenaga Kerja Pada Pekerjaan Pylon Proyek Pembangunan Jembatan Siak IV Pekanbaru - Azizah Fil Ahlia; Rian Tri Komara Iriana; Alfian Kamaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Labors productivity greatly impacts the success of construction project. Therefore, it is imperative to perform analysis on the determination of labors productivity. The purpose of this research is to find out the coefficient value of labors on the Siak IV Bridge project and to assess coefficient value of labors that has been obtained between coefficient value on the minister of public works regulation No. 28/PRT/M/2016 and project contract document. So, to find the coefficient value, the researcher must know the labor’s productivity whis is important factor for the success of a project, so it needs to ways examine to measure labors productivity in a project. In this study, the measurement of labors productivity was carried out in the upstream and downstream pylon jobs in segment 9 with sub workings reinforcement, formwork, casting by doing observation in the field. Field observation has purpose to find out timing which is needed to finish sub workings. Coefficient which is obtained from result analysis on front pylon for sub working reinforcemant is 0.414 OH for labors, 0.160 OH for workers, 0.032 OH for foreman. On formwork sub working it shows 0.324 OH for labors, 0.88OH for workers, 0.029 OH for foreman. Then the result shows on back pylon analysis sub working reinforcement, 0.432 OH for labors, 0.170 OH for workers, 0.033 OH for foreman. On formwork shows 0.148 OH for labors, 0.049 OH for workers and 0.025 OH for foreman. Coefficient for casting sub working shows 0.304 OH for labors, 0.083 OH for workers and 0.028 OH for foreman.Keywords: Coefficient, Labors, Productivity, Siak IV Bridge Construction.